AVOIDING RISK IN WORKING CAPITAL CREDIT DISTRIBUTION IN INDONESIA - Aloysius Deno Hervino (Economic Journal of Emerging Markets, 2011)
This research analyzes risk avoidance behaviour of banking institutions in distributing working capital loan in Indonesia. Using Autoregressive Distributed Lag Error Correction Model, this paper uncovers three findings. First, in the short run, risk avoidance in working capital loan distribution depends on inter-call banking money market and Sertifikat Bank Indonesia. Second, following banking regulation after 1997 crisis, banks have become more careful in distributing credits, with SBI as a substitution instrument and inter-call banking money market as a complement instrument to spread the risk. Third, all explanatory variables take an average of 6 days or 1 week to influence bank’s risk avoidance behaviour.Keywords:     Risk avoidance, working capital distribution, banking institutions JEL classification numbers: C32, C52, D81, E51